### Eamcet - Maths - Partial Differentiation

If f(x,y,z)=√(yz)+ √(zx)+ √(xy) then xfx+yfy+zfz=

A.  0

B.  √x+√y+√z

C.  f(x,y,z)

D.  2f(x,y,z)

f(x,y,z)

Explanation :
No Explanation available for this question

If au+b=a2x+y then uxuy=

A.  0

B.  1

C.  2

D.  None

1

Explanation :
No Explanation available for this question

If u=(y+sin x)3+(y-sin x)2,then uxx=

A.  uyycos2x-ux tan x

B.  uyycos2x+ux tan x

C.  uxxcos2x-uyy tan x

D.  none

uyycos2x-ux tan x

Explanation :
No Explanation available for this question

If u=(ax+by)2-(x2+y2) and a2+b2=1 then uxx+uyy=

A.  1

B.  0

C.  2ab

D.  -2

-2

Explanation :
No Explanation available for this question

If V=πr2h then rVr+2hVh=

A.  4V

B.  V

C.  2V

D.  V2

4V

Explanation :
No Explanation available for this question

If u=x2+y2+z2,x=et,y=et sin t,z=et cos t then du/dt=

A.  e2t

B.  4e2t

C.  u

D.  None

4e2t

Explanation :
No Explanation available for this question

If u3(1+a3)=8(x+ay+b)3 then u3x+u3y=

A.  8

B.  2

C.  6

D.  4

8

Explanation :
No Explanation available for this question

If f(x,y)=xy+(1/x)+(1/y) then fxx?fyy-fxy2 at (1,1) is

A.  4

B.  0

C.  1

D.  3

3

Explanation :
No Explanation available for this question

If r2=(x-a)2+(y-b)2 then rxx+ryy=

A.  1/r

B.  1/r2

C.  r2

D.  r

1/r

Explanation :
No Explanation available for this question

If f(x,y)=x2Tan-1(y/x)-y2 Tan-1(x/y),x≠0,y≠0 then fxy=

A.  x2+y2/ x2+y2

B.  x2-y2/ x2+y2

C.  x-y2/ x2+y2

D.  none

x2-y2/ x2+y2

Explanation :
No Explanation available for this question

If V is the volume of a rectangular box with edges x,y,z then Vxyz=

A.  0

B.  1

C.  x+y+z

D.  none

1

Explanation :
No Explanation available for this question

If f=x2yz+y2zx+z2xy then fxyz=

A.  0

B.  2

C.  2x

D.  2(x+y+z)

2(x+y+z)

Explanation :
No Explanation available for this question

If z(x,y) is the implicit function defined by x3+y3+z3=3xyz then xzx+yzy=

A.  0

B.  -z

C.  Z

D.  3z

Z

Explanation :
No Explanation available for this question

If u=3(lx+my+nz)2-(x2+y2+z2) and l2+m2+n2=1 then uxx+uyy+uzz=

A.  0

B.  u

C.  2u

D.  None

0

Explanation :
No Explanation available for this question

If Z=1n(1+xr+yr) then Zxy=

A.  -Zx Zy

B.  Zx Zy

C.  Zx2

D.  Zy2